KETELADANAN KEHIDUPAN RUT DAN PENGARUHNYA BAGI WANITA KRISTEN MASA KINI - Sriwahyuni24; B, Yesaya; Tampubolon, Timotius (STT Ebenhaezer Tanjung Enim, 2024)
The purpose and objective of the Community Service program are as follows: (1) to provide a correct understanding of Ruth's exemplary role; (2) factors that cause women to not appear much in general; (3) women are no less than men; (4) Ruth's exemplary role is important in service; (5) a good spiritual journey will lead someone to God's intentions and plans; (6) Ruth is a woman who is tough, loyal, obedient and loves God; (7) there are methods used in serving women. The solutions used to overcome these problems are as follows: (1) providing gradual assistance in overcoming discrimination against women; (2) providing teaching, namely spiritual values ​​through existing seminars; (3) the role of the church and government in protecting women who are suspected of discrimination and facilitating them in their rights and obligations as women. (4) Where God and the state (UUD) women and men have the same rights and obligations The methods used in implementing Community Service activities include the following: (1) obtaining information from Postgraduate students and monitoring by supervising lecturers; (2) pre-research; (3) interviews; (4) preparation of supervising lecturers together with Postgraduate students; (5) implementation days; (6) evaluation and follow-up consultations The results of the Community Service Activity program are: (1) knowing about the role of Christian women in the church, family and community environment; (2) training and providing opportunities for women to continue to contribute both in the church and the community environment; (3) being able to be a blessing to many people; (4) becoming women who can serve together with men in many ways.